(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2026)
This research investigates the effectiveness of expression-based instruction in enhancing English speaking competence among students in underperforming rural schools of Narpay district. Learners in these schools often struggle with oral communication due to limited exposure to authentic English, low self-confidence, and traditional grammar-focused pedagogy. The study employs a quasi-experimental design with pre- and post-speaking assessments, classroom observations, and student feedback analysis. The experimental group received systematic instruction in functional expressions, discourse markers, and conversational routines, while the control group continued traditional grammar-based instruction. The findings reveal a significant improvement in fluency, coherence, lexical range, and interactional competence among the experimental group. Additionally, students demonstrated higher motivation and reduced anxiety during speaking tasks. The study concludes that expression-based pedagogy can serve as an effective tool for developing communicative competence in rural EFL contexts.